Does SDG 6 matter in a water-abundant country like Brazil? - Celeste, Alcigeimes B. (2023)
Alcigeimes B. Celeste, Dr.Eng. POLICY SEMINAR Water & SDGs - Downscaling WATer relevant SDGs (DWAT-SDGs) 2023 UN Water Conference Side Event Jointly organized with the International Water Resources Association (IWRA) MAR 20, 2023 - 10:00 TO 11:00AM EDT